Student sports clubs as a factor in university students’ enhancing social adaptation - Dmitriy O. Zhdanovich, Viktor K. Pelmenev, (Opción, 2019)
The purpose of the article is to develop a model for introducing student sports clubs (SSCs) as a means of enhancing social adaptation to the reference environment for new students entering higher educational institutions via a sociological survey method. As a result, among the students actively involved in the work of SSC, 36.1% note that this type of activity has a positive effect on their social adaptation to the university. In conclusion, the indicators of socio-psychological adaptation of students are very dynamic.